Impedimetric Humidity Sensor Based on Nanohybrid Composite of Conducting Poly(diphenylamine sulfonic acid) - Zor, Sule Dinc; Cankurtaran, Husnu (HINDAWI LTD, 2016)
Interdigitated thin film humidity sensors have been prepared using organic/inorganic nanocomposites of poly(diphenylamine sulfonic acid) (PSDA), 3-mercaptopropyltrimethoxysilane (MPTMS), and nano-ZnO. Humidity sensing properties of the sensors, regarding the effect of nano-ZnOaddition and the applied alternating current frequency, were studied by impedance measurements in the frequency range of 100 Hz-1 kHz. It was found that the sensing properties of the ZnO based nanocomposite sensors had better properties than those of the PSDA-MPTMS based composite due to contribution of the nanomaterial. Good sensitivity (about three orders' magnitude change in impedance), linear response, rapid response (90 s) and recovery (60 s), and low hysteresis within 4% as well as good repeatability and stability in the range from 12% to 95% RH were obtained.
Keywords: QUARTZ-CRYSTAL MICROBALANCE; SENSING PROPERTIES; ELECTRICAL-PROPERTIES; GAS; TIO2; POLYANILINE; SENSITIVITY; MECHANISM; COPOLYMER; POLYMERS; Engineering; Instruments & Instrumentation